Causas del bajo nivel de uso de la metodología BIM, sujeto de estudio 23 proyectos privados del Ecuador - Claudio Espinel, Yadira Estefany (2022)
The BIM methodology globally controls projects in the construction industry so that errors can be reduced, collaborative work facilitated, and productivity improved in the project life cycle. Through studies carried out in Ecuador, the authors have determined a low level of use of this methodology where the causes for the BIM implementation to have a significant boom in its development have not yet been determined. This research work aims to identify the reasons that interfere with the low level of use of the methodology by analyzing the planning and design phase in 23 Ecuadorian projects. To this end, a survey was prepared based on the deficiencies detected based on studies on the low level of use of the methodology, which was applied to different professionals who participated in the projects. The data obtained when analyzed with DEMATEL allowed us to determine the most critical barriers, such as the reluctance to change, prioritizing the use of traditional methods, the high cost of investment, the lack of a standard by the government, and the lack of personnel with skills in BIM. From this analysis, there is a need to start introducing and strengthening BIM knowledge among both professionals and students since BIM technology promises to be the future of project management